Algorithms and Discrete Applied Mathematics First International Conference, CALDAM 2015, Kanpur, India, February 8-10, 2015. Proceedings - Ganguly, Sumit; Krishnamurti, Ramesh; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book collects the refereed proceedings of the First International Conference onon Algorithms and Discrete Applied Mathematics, CALDAM 2015, held in Kanpur, India, in February 2015. The volume contains 26 full revised papers from 58 submissions along with 2 invited talks presented at the conference.The workshop covered a diverse range of topics on algorithms and discrete mathematics, including computational geometry, algorithms including approximation algorithms, graph theory and computational complexity.
Obstruction Characterizations in Graphs and Digraphs -- Approximation Algorithms -- A PTAS for the Metric Case of the Minimum Sum-Requirement Communication Spanning Tree Problem -- Constant Approximation for Broadcasting in k-cycle Graph -- Computational Geometry -- Three paths to point placement -- Vertex Guarding in Weak Visibility Polygons -- On Collections of Polygons Cuttable with a Segment Saw -- Rectilinear path problems in the presences of rectangular obstacles -- Computational Complexity -- Parameterized Analogues of Probabilistic Computation -- Algebraic Expressions of Rhomboidal Graphs -- Solving Hamiltonian Cycle by an EPT Algorithm for a Non-sparse Parameter -- Graph Theory. New Polynomial Case for Efficient Domination in P 6-free Graphs -- Higher-Order Triangular-Distance Delaunay Graphs: Graph-Theoretical Properties -- Separator Theorems for Interval Graphs and Proper Interval Graphs -- Bounds for the b-Chromatic Number of Induced Subgraphs and G e -- New Characterizations Of Proper Interval Bigraphs and Proper Circular Arc Bigraphs -- On Spectra of Corona Graphs -- Axiomatic Characterization of the Median and Antimedian Functions on Cocktail-Party Graphs and Complete Graphs -- Tree Path Labeling of Hypergraphs A Generalization of the Consecutive Ones Property -- On a special class of boxicity 2 graph -- Algorithms -- Associativity for Binary Parallel Processes: a Quantitative Study -- A Tight Bound for Congestion of an Embedding.-Auction/Belief propagation algorithms for constrained assignment problem -- Domination in some subclasses of bipartite graphs -- Bi-directional Search for Skyline Probability -- Cumulative vehicle routing problem: a column generation approach -- Energy Efficient Sweep Coverage with Mobile and Static Sensors -- Generation of Random Digital Curves using Combinatorial Techniques.
Keywords: Algorithms; Data structures (Computer science).; Computer science—Mathematics.; Numerical analysis; Computer graphics; Algorithm Analysis and Problem Complexity; Data Structures; Discrete Mathematics in Computer Science; Numeric Computing; Computer Graphics; Algorithms